SUPERVISI AKADEMIK KEPALA MADRASAH DALAM MENINGKATKAN MUTU PMMBELAJARAN DI MTs MINHAJUTH THULLAB SIDOMULYO KECAMATAN MESUJI KABUPATEN MESUJI - Munawir Fathoni (UNISAN JURNAL, 2023)
This study aims to determine the role of the madrasa principal's academic supervision in improving the quality of learning at MTs Minhajuth Thullab Sidomulyo Kecamatan Mesuji Kabupaten Mesuji. This research uses a qualitative approach with a case study method. Data was collected through interviews with madrasa heads, teachers, and students, as well as learning observations. The results of the study show that the academic supervision of the madrasa head has an important role in improving the quality of learning. Madrasah heads are able to motivate teachers in carrying out learning innovations, provide constructive feedback, and identify problems that occur in the learning process. In addition, madrasa heads are also able to facilitate the development of teacher competencies through training and mentoring. In this case, collaboration between madrasa heads and teachers is needed to achieve the same goal, namely to improve the quality of learning. Therefore, it is suggested that madrasa heads pay attention to the role of academic supervision in carrying out their duties as madrasa leaders, as well as improve communication and cooperation with teachers in the learning process.